2009
DOI: 10.1007/s10658-009-9475-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin and umbelliferone on the transcript level of Penicillium expansum genes involved in patulin biosynthesis

Abstract: Penicillium expansum is commonly associated with patulin accumulation in pome fruits. In in vitro studies, two phenolic compounds (quercetin and umbelliferone) proved to be effective in reducing patulin accumulation, particularly when applied in combination, without consistently affecting mycelial growth. To investigate the mode of action of quercetin and umbelliferone, the expression of five genes likely involved in patulin biosynthesis was evaluated using real-time PCR in the presence and absence of the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 32 publications
3
35
0
2
Order By: Relevance
“…(6) showed that the expression of genes of the secondary metabolism is strictly controlled by nutrients ,inducers, products, metals and growth rate, and in most cases, regulation is at transcription level. This assumption was also supported by (14).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…(6) showed that the expression of genes of the secondary metabolism is strictly controlled by nutrients ,inducers, products, metals and growth rate, and in most cases, regulation is at transcription level. This assumption was also supported by (14).…”
Section: Resultssupporting
confidence: 55%
“…This suggested to us that other genes involved in patulin biosynthesis . (20) who was reported that the absence of genes in the patulin producing fungus Byssochlamys fulva resulted in its inability to produce toxin, the result of (14) provide evidence that quercetin and umbelliferone (phenolic compounds) do not seem to affect primary fungal metabolism, but reduce patulin production by acting on its biosynthetic pathway. Relative expression idh , genes in the toxigenic strain P.expansum grown for six days on LTB supplemented with B. breve and L. salivarius.…”
Section: Resultsmentioning
confidence: 99%
“…cDNAs were synthesized using a PrimeScript RT Reagent Kit (Takara Bio, Shiga, Japan). Reactions of reverse transcription were carried out using gene-specific primers 29) in a thermal cycler, GeneAmp PCR System 9700 (Invitrogen Life Technologies, Carlsbad, CA).…”
Section: )mentioning
confidence: 99%
“…At this concentration, mycelial growth of P. expansum and T. purpureogenus was still evident, however that of A. implicatum was completely inhibited. Similarly, Sanzani, Schena, Nigro, De Girolamo, and Ippolito (2009) reported that quercetin and umbelliferone (two phenolic compounds) inhibited the in vitro production of PAT but did not affect P. expansum growth. However, Kumar and Prasad (1992) suggested that growth and aflatoxin production by A. flavus are proportionate processes.…”
Section: Discussionmentioning
confidence: 93%